Isolasi Dan Karakterisasi Bakteri Dari Tanah Bakaran Sampah - Toberni S Situmorang; Rahmiati Rahmiati; Helen Anjelina Simanjuntak (Mahesa Research Center, 2022)
Bacteria are microorganisms that are abundant in the environment. Isolation of bacteria has been carried out from various sources of water, air and soil. Soil is a material that is rich in nutrients needed by various organisms including bacteria, which are capable of producing secondary metabolites that can be utilized in various fields. Different sources of isolates will produce different characteristics of the bacteria. This research aims to determine the type and characterization of bacteria originating from burnt waste soil. The research was conducted using a qualitative descriptive method. The soil sample used is burnt waste soil. The results showed that 6 bacterial isolates from burnt waste soil had different characteristics, namely TBS01, TBS02, TBS03, TBS04, TBS05, TBS06. Microscopic identification results showed that the bacterial isolates TBS01 and TBS02 were gram-negative bacteria and the other isolates included gram-positive bacteria. Differences in morphological and microscopic characteristics indicate different types of bacterial isolates.